Prevalence and trend of potential drug–drug interaction among children with depression in U.S. outpatient settings. Issue 4 (12th September 2019) - Lai, L Leanne; Alvarez, Goar; Dang, Linh; Vuong, Dung; Ngo, Vy; Jo, Yailin; Koh, Leroy
Abstract: Objectives: Oftentimes, children with depression are treated with multiple medications. The potential risk of drug–drug interactions (DDI) and its unexpected adverse effects can develop as a result. Due to ethical concerns and restrictions on conducting clinical trials in the pediatric population, there is little data available about the efficacy and safety of drug use, especially in combination with other medicines. This study aims to examine the prevalence and trend of potential DDI when prescribing for children with depression in the U.S. outpatient settings. Methods: Data were extracted from the National Ambulatory Medical Care Survey (NAMCS). Children of 18 years old or younger with a diagnosis of depression were analysed. Drug Facts and Comparisons database was used to identify major or moderate severity drug interactions. Data trends were analysed using the Mann-Kendall trend test. Key findings: Estimated 1.28 million children were diagnosed with depression in the US outpatient settings between 2010 and 2014. More than a quarter of the children with a diagnosis of major depressive disorder and receiving medications had a potential major or moderate drug–drug interaction. The upward trend of DDI is visible. However, Mann-Kendall test showed no significant monotonic relationship (Kendall's tau = 0.32; P = 0.45). Conclusions: This study provided significant and real-world evidence about the high prevalence rate of DDI in children receiving depression treatment. There is an urgent need to detect, assess and analyse DDIs before clinical medications are administered. Ultimately, it aims to improve patient care and safety in relation to the use of medicines.